Inverse Perfusion Requirements of Supra- and Infratentorial Brain Metastases Formation - Schneider, Tanja; Kemmling, André; Schroeder, Julian; Pantel, Klaus; Glatzel, Markus; Schoen, Gerhard; Mohme, Malte; Fiehler, Jens; Gellißen, Susanne (Frontiers in Neurology, 2018)
Background and Aims: Vascular border zones and the grey-white matter junction are preferred sites for the development of brain metastases (BM), whereas microvascular lesions are known to be a protective factor. In this proof of concept study, we aim to study the relationship of blood perfusion and the spatial distribution of BM. Materials and Methods: An average CT perfusion atlas of 107 healthy patients was created. Voxel-wise reference perfusion values were extracted from BM-negative and BM-positive regions in a second cohort of 100 untreated patients harboring 809 BM confirmed by MRI. A comparison of regional perfusion values was performed using the independent t-test. Results: In contrast to supratentorial BM that develop preferably in areas with lower CBV/CBF and longer MTT/TTP compared to the average regional perfusion (p<0.001), infratentorial BM showed a higher CBV/CBF and shorter MTT/TTP (p<0.001). Conclusion: Our results imply differing pathophysiological mechanisms underlying supra- and infratentorial BM spreading. The inverse perfusion patterns may result from differences in vascular supply, hemodynamic requirements, and/or production of pro-angiogenic factors.